2016
DOI: 10.1186/s12951-016-0215-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gadolinium-based nanoparticles on nuclear DNA damage and repair in glioblastoma tumor cells

Abstract: BackgroundTumor targeting of radiotherapy represents a great challenge. The addition of multimodal nanoparticles, such as 3 nm gadolinium-based nanoparticles (GdBNs), has been proposed as a promising strategy to amplify the effects of radiation in tumors and improve diagnostics using the same agents. This singular property named theranostic is a unique advantage of GdBNs. It has been established that the amplification of radiation effects by GdBNs appears due to fast electronic processes. However, the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 86 publications
6
67
3
Order By: Relevance
“…However, because of the specificity of tumors and the side effects of these methods, treatment is far from satisfactory. With the emergence of, for example, drug resistance ( 3 ) and DNA damage repair ( 29 , 30 ) during the treatment, the therapeutic effect is compromised in cancers when using monotherapy. Therefore, it is necessary to use combinations of two or more therapeutic methods that act via different mechanisms to produce synergistic effects to treat cancers.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the specificity of tumors and the side effects of these methods, treatment is far from satisfactory. With the emergence of, for example, drug resistance ( 3 ) and DNA damage repair ( 29 , 30 ) during the treatment, the therapeutic effect is compromised in cancers when using monotherapy. Therefore, it is necessary to use combinations of two or more therapeutic methods that act via different mechanisms to produce synergistic effects to treat cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Our work and previous studies 32,33 make clear that the radiosensitization under proton irradiations, unlike photon irradiations where physical interactions can also contribute to the effect, is highly unlikely to originate from direct or indirect damage to the DNA. As a result, the alternative or supplementary mechanisms that have been proposed for photon irradiations, such as increased oxidative stress, mitochondria function disruption, 36,37 and lysosomal rupture, 38 might be more important in the case of proton irradiations, and ultimately the key to understanding radiosensitization with heavy metal nanoparticles bombarded with ions.…”
Section: Discussionmentioning
confidence: 99%
“…Kusiak and Zaborski (2012) 50, 30, 20 and 20 phr, respectively, are found to strongly absorb X-rays. Stefancikova et al (2016) have studied the role of gadolinium-based nanoparticles as radiosensitizers and have shown that the radiosensitization mediated by gadolinium-based nanocomposite is a cytoplasmic event, independent of nuclear DNA damage.…”
Section: Introductionmentioning
confidence: 99%